Study on Annual Internal Radiation Dose from Consumption of Sweet Potatoes Contaminated by 134 Cs - Idam Arif; Siti Nurul Khotimah; Octolia Tobigasa Tambunan; Poppy Intan Tjahaja (Indonesian Journal of Physics, 2010)
The transfer of 134Cs from soil to sweet potato crops has been investigated. Sweet potato crops were cultivated in soil contaminated by 134Cs with concentration of 167.62 Bq/g as well as in non-contaminated soil as control. The 134Cs activity concentrations of leaves, stems, roots, tubers and the whole plant were determined every week up to 16 weeks. 134Cs activity concentrations of soil in root zone and outside root zone were also determined. The maximum transfer factor for the whole sweet potato plants takes place at the second week with TF value of 1.277. The maximum TF value for each parts are roots (18.448), tubbers (13.153), stems (1.241), and leaves (0.746). Annual equivalent dose was calculated based on the activity of sweet potato plants at harvest time. This research obtained annual internal radiation dose from consumption of sweet potatoes contaminated by 134Cs of 0.0185 mSv/year. This value compared with average annual dose limits recommended by BAPETEN, IAEA and ICRP respectively was 0.14%, 0.37%, and 0.19%.